Evaluating the clinical effectiveness of new beta-lactam/beta-lactamase inhibitor combination antibiotics: A systematic literature review and meta-analysis - Geneva M. Wilson; Margaret A. Fitzpatrick; Kyle Walding; Beverly Gonzalez; Marin L. Schweizer; Katie J. Suda; Charlesnika T. Evans (Cambridge University Press, 2021)
Abstract Background: Ceftazidime/avibactam (C/A), ceftolozane/tazobactam (C/T), imipenem/relebactam (I/R), and meropenem/vaborbactam (M/V) combine either a cephalosporin (C/T and C/A) or a carbapenem antibiotic (M/V and I/R) with a β-lactamase inhibitor. They are used to treat carbapenem-resistant Enterobacterales (CRE) and/or multidrug-resistant Pseudomonas aeruginosa (MDRPA). Objective: We compared the pooled clinical success of these medications to older therapies. Methods: PubMed and EMBASE were searched from January 1, 2012, through September 2, 2020, for C/A, C/T, I/R, and M/V studies. The main outcome was clinical success, which was assessed using random-effects models. Stratified analyses were conducted for study drug, sample size, quality, infection source, study design, and multidrug-resistant gram-negative organism (MDRGNO) population. Microbiological success and 28- and 30-day mortality were assessed as secondary outcomes. Heterogeneity was determined using I2 values. Results: Overall, 25 articles met the inclusion criteria; 8 observational studies and 17 randomized control trials. We detected no difference in clinical success comparing new combination antibiotics with standard therapies for all included organisms (pooled OR, 1.21; 95% CI, 0.96-1.51). We detected a moderate level of heterogeneity among the included studies I2 = 56%. Studies that focused on patients with CRE or MDRPA infections demonstrated a strong association between treatment with new combination antibiotics and clinical success (pooled OR, 2.20; 95% CI, 1.60-3.57). Conclusions: C/T, C/A, I/R, and M/V are not inferior to standard therapies for treating various complicated infections, but they may have greater clinical success for treating MDRPA and CRE infections. More studies that evaluate the use of these antibiotics for drug-resistant infections are needed to determine their effectiveness.